Systematic review with meta‐analysis: the management of chronic refractory pouchitis with an evidence‐based treatment algorithm. Issue 5 (23rd December 2016) - Segal, J. P.; Ding, N. S.; Worley, G.; Mclaughlin, S.; Preston, S.; Faiz, O. D.; Clark, S. K.; Hart, A. L.
Summary: Background: Restorative proctocolectomy with ileal pouch anal anastomosis (IPAA) is considered the procedure of choice in patients with ulcerative colitis (UC) refractory to medical therapy. The incidence of pouchitis is 40% at 5 years. Ten to 15% of patients with pouchitis experience chronic pouchitis. Aim: To determine the efficacy of medical therapies for the treatment of chronic refractory pouchitis in patients undergoing IPAA for UC. Methods: A systematic computer‐assisted search of the on‐line bibliographic database MEDLINE and EMBASE was performed between 1966 and February 2016. All original studies reporting remission rates following medical treatment for chronic pouchitis were included. All study designs were considered. Remission was defined according to the individual study. Remission endpoints ranged from 15 days to 10 weeks. Chronic pouchitis was defined by each study. Results: Twenty‐one papers were considered eligible. Results from all studies combined suggested that overall remission was obtained in 59% of patients (95% CI: 44–73%). Antibiotics significantly induced remission in patients with chronic pouchitis with 74% remission rate (95% CI:56–93%), ( P < 0.001). Biologics significantly induced remission in patients with chronic pouchitis with 53% remission rate (95% CI:30–76%), ( P < 0.001). Steroids, bismuth, elemental diet and tacrolimus all can induce remission but failed to achieve significance. Faecal microbiota transplantation in a single study was not found to achieve remission. Conclusions: Treatment of chronic refractory pouchitis remains difficult and is largely empirical. Larger randomised controlled trials will help aid the management of chronic pouchitis.